INDIVIDUAL DIFFERENCES IN WORKING MEMORY PERFORMANCE: «OVERLOAD» EFFECT - Yuri G. Pavlov (Образование и наука)
The aim of this research is to study the relationship betweenfrontal midline theta rhythm changes and individual differences in working memory performance.Methods. The methods involve behavioural testing on the basis of the program for a presentation of stimulus and registration of answers «PsyTask»; method of EEG (electroencephalography); a technique of measurement of efficiency of working memory; the comparative analysis. Software packages EEGLab for Matlab and Fieldtrip are applied while data processing.Results. After the behavioral test all subjects were separated into 2 groups according to their performance: with «highly productive» and «low productive» memory. Specially prepared author’s complete set of the tasks which complexity varied from average to ultrahigh level was offered to participants of experiment –students and employees of the Ural Federal University and Ural Legal Institute of the Ministry of Internal Affairs. Working memory tasks included sets of verbal stimuli for memorizing in strict order without any mental manipulation and sets of similar stimuli for memorizing in alphabetical order (with manipulations). Measured characteristics of theta-rhythm of EEG during information deduction in memory were compared of two groups’ representatives. The obtained data has shown rather uniform and similar dynamics of decrease in quantity of right answers in process of increasing tasks’ complexity. However, changes of a thetarhythm in different groups had sharply expressed distinctions. «Highly productive» examinees have systematic expansion of a theta-rhythm in the central assignments with stabilisation on the most difficult tasks; «low productive» – while tasks performance of average complexity, a sharp falling of theta-rhythm activity is observed after achievement of its maximum activation.Scientific novelty. The working memory «overload» effect and its EEG correlates are demonstrated on a big sample of subjects.Practical significance. The work urgency is connected with increasing loadings for memory of the person in a modern information society. Research of the operating memory mechanisms is especially important for finding-out of pupils’ possibilities to renew their knowledge and independently solve various cognitive problems, including planning, orientation in verbal space, a mental manipulation objects, etc.